Harnessing the Potential of Metallic Nanoparticles for Modulating the Tumor Microenvironment and Immune Responses in Breast Cancer Immunotherapy - Prajapati, Shatrudhan; Yadav, Shikha (Clinical Cancer Drugs, 2025)
Utilizing the body's immune system to combat cancer has become a viable tactic known as cancer immunotherapy. Metallic nanoparticles, or MNPs, have drawn a lot of interest because of their special qualities and their uses in cancer immunotherapy. The manufacturing processes of MNPs, their function in altering the tumor microenvironment (TME), and their capacity to control immune cells for potent anticancer effects are all thoroughly covered in this review. The review underscores the benefits of MNPs in surmounting obstacles linked to traditional cancer treatments, including toxicity, resistance, and off-target effects. It also goes over the different ways that MNPs modulate the immune system, For example, by generating reactive oxygen species (ROS), reducing glutathione (GSH) levels, and improving hypoxia. The research also examines the ability of MNPs to enhance the maturation of dendritic cells, shift macrophages towards an M1 phenotype, stimulate T-cell responses, and aid in the transportation of natural killer (NK) cells. The investigation is focused on understanding the synergistic effects of MNPsIn conjunction with other immunotherapeutic approaches, such as checkpoint inhibitors and cell-based treatments, in order to generate potent immune responses against cancer.
Keywords: hypoxia